An evaluation of adhesive sample holders for advanced crystallographic experiments. (1st September 2014) - Mazzorana, Marco; Sanchez‐Weatherby, Juan; Sandy, James; Lobley, Carina M. C.; Sorensen, Thomas
<x xml:space="preserve">Abstract</x> The hydration state of macromolecular crystals often affects their overall order and, ultimately, the quality of the X‐ray diffraction pattern that they produce. Post‐crystallization techniques that alter the solvent content of a crystal may induce rearrangement within the three‐dimensional array making up the crystal, possibly resulting in more ordered packing. The hydration state of a crystal can be manipulated by exposing it to a stream of air at controlled relative humidity in which the crystal can equilibrate. This approach provides a way of exploring crystal hydration space to assess the diffraction capabilities of existing crystals. A key requirement of these experiments is to expose the crystal directly to the dehydrating environment by having the minimum amount of residual mother liquor around it. This is usually achieved by placing the crystal on a flat porous support (Kapton mesh) and removing excess liquid by wicking. Here, an alternative approach is considered whereby crystals are harvested using adhesives that capture naked crystals directly from their crystallization drop, reducing the process to a one‐step procedure. The impact of using adhesives to ease the harvesting of different types of crystals is presented together with their contribution to background scattering and their usefulness in dehydration experiments. It is concluded that adhesive supports represent a valuable tool for mounting macromolecular crystals to be used in humidity‐controlled experiments and to improve signal‐to‐noise ratios in diffraction experiments, and how they can protect crystals from modifications in the sample environment is discussed.